The Effect of Destination Brand Experience on Tourist Citizenship Behavior: With Emphasis on the Role of Tourism Destination Brand Attitude, Passion and Commitment (Case Study: Isfahan) - Saied Saieda Ardakani; Amirreza konjkav monfared; Farzaneh Zarabkhaneh (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2021)
Tourists' experience of a tourism destination brand is the basis of many of their behavioral consequences. Therefore, in the present study, the effect of tourism destination brand experience on tourist citizenship behaviors with Emphasis on the role of three variables: passion, commitment, and attitude of tourism destination brand has been investigated. The present research is applied in terms of purpose and descriptive-survey in terms of research method. The statistical population of this study was domestic tourists in Isfahan, from which 182 people were selected as a sample, and the necessary data were collected through the distribution of questionnaires. The results of data analysis using P.L.S. software have shown that the experience of the tourism destination brand has a positive and significant effect on the enthusiasm, attitude, and commitment of the tourism destination brand. The results also show that the commitment and attitude of the tourism destination brand have a direct and significant effect on the citizenship behavior of the tourism destination brand, while the brand enthusiasm has a direct impact on the citizenship behavior of tourists both directly and through the commitment and attitude of the tourism destination brand. In addition, the results showed that the enthusiasm of the tourism destination brand had the greatest impact on the citizenship behavior of tourists compared to the other two variables